Jamaica. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Jamaica during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as animal nutrition, export, silvopastoral, good agricultural practices, agribusiness, financing, fodder and pest control, like coffee rust. Finally, support was given to the inclusion of young people in agricultural issues and in the improvement of the value chains of coffee, pumpkins, hot peppers, chenette, sweet potatoes and mangoes.